OP0037 ASSOCIATION BETWEEN BONE MARROW EDEMA AND STRUCTURAL PROGRESSION IN THE SAME QUADRANT IN AXIAL SPONDYLOARTHRITIS – 5-YEAR DATA FROM THE DESIR COHORT. (June 2019) - Rodrigues-Manica, Santiago; Sepriano, Alexandre; Ramiro, Sofia; Landewé, Robert B.M.; Claudepierre, Pascal; Moltó, Anna; Dougados, Maxime; Lunteren, Miranda van; Heijde, Désirée van der
Abstract : Background: The overall presence of inflammation in the MRI-SIJ is associated with overall 5-year radiographic damage in patients with axSpA 1 . But we do not know if a bone marrow edema (BME) lesion leads to a structural lesion at the same place (i.e. in the same quadrant). Objectives: To investigate the association between BME and structural progression in the same quadrant of the SIJ, over time. Methods: Patients from the DESIR cohort (early axSpA according to the rheumatologist) with ≥2 consecutive MRI-SIJ (out of baseline, 2 and 5 years), were included. Each image was independently scored by 3 trained central readers blinded to chronological order. BME was considered present in a time point if detected in ≥1/6 slices in each of the 8 quadrants. The prevalence of BME (yes/no) and structural lesions (sclerosis, erosions, fatty lesions and ankylosis; all yes/no) defined, per quadrant, by the agreement of ≥2 out of 3 readers, was described at BL and at 5 years. The longitudinal association between BME and each of the structural lesions in the same quadrant was tested in time-lagged multilevel Generalized Estimating Equation (GEE) models with autoregression, taking individual reader data into account, and adjusting for clinical variables selected a priori on clinical grounds (age, gender, disease activity and treatment). Results: In total, 197 patients were included (age 34 (SD 9) years, 48% male and 61% HLA-B27 positive). While BME and fatty lesions were evenly distributed across quadrants, erosions and sclerosis occurred preferably in the iliac side (i.e. Q1 and Q4) (Table 1). The prevalence of BME decreased over time (baseline range: 11%-16%; 5-year range: 7%-14%), while erosions (baseline range: 2%-23%; 5-year range: 3%-28%) and especially fatty lesions (baseline range: 4%-14%; 5-year range: 9%-21%) increased. Ankylosis and sclerosis were rare in this early axSpA cohort. In the multivariable models, BME was longitudinally associated with sclerosis (OR:1.7 (95% CI: 1.0;3.2)), erosions (2.0 (1.5;2.5)) and fatty lesions (1.7 (1.1;2.5)). The possible association with ankylosis could not be tested due to too low number of lesions (Table 2). Conclusion: We here demonstrate that in early axSpA-patients inflammation in one SIJ quadrant leads to structural damage in the same quadrant. This finding reinforces the pathophysiological implications of inflammation in axSpA. Reference: [1] Dougados, et al. Ann Rheum Dis. 2017;76(11):1823–1828. Disclosure of Interests: Santiago Rodrigues-Manica Grant/research support from: Novartis, MSD, Speakers bureau: Novartis, Alexandre Sepriano: None declared, Sofia Ramiro Grant/research support from: MSD, Consultant for: AbbVie, Lilly, MSD, Novartis, Pfizer, Sanofi, Speakers bureau: AbbVie, Lilly, MSD, Novartis, Pfizer, Sanofi, Robert B.M. Landewé: None declared, Pascal Claudepierre Consultant for: Honoraria from Novartis as steering committe of this survey, Anna Moltó: None declared, maxime dougados Grant/research support from: Eli Lilly and Company, Pfizer, AbbVie, and UCB Pharma, Consultant for: Eli Lilly and Company, Pfizer, AbbVie, and UCB Pharma, Miranda van Lunteren: None declared, Désirée van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Daiichi, Eli-Lilly, Galapagos, Gilead, GlaxoSmithKline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, Union Chimique Belge